2007
DOI: 10.1007/s10534-006-9045-8
|View full text |Cite
|
Sign up to set email alerts
|

“Trade-off” in Antarctic bacteria: limnetic psychrotrophs concede multiple enzyme expressions for multiple metal resistance

Abstract: The present study examines the metal and antibiotic resistant bacteria in ice and water from lakes east and west of the Indian base camp (Maitri) in Antarctica. The isolates from western and eastern lakes showed distinct geographical differences in properties like metal resistance and enzyme expression. This may be attributed to high organic loading in the lakes on the west of Maitri. However, there was no marked geopraphical distinction in antibiotic resistance between the lakes. Bacteria from the lakes on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…catalase, oxidase, amylase, protease, gelatinase, urease and nitrate reductase) results were correlated with the metal ion resistance profiles of the distinct bacterial isolates, as conducted previously by De Souza et al . (). In general, bacterial isolates exhibiting multiple‐metal resistance had a considerably wider range of enzymatic activities (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…catalase, oxidase, amylase, protease, gelatinase, urease and nitrate reductase) results were correlated with the metal ion resistance profiles of the distinct bacterial isolates, as conducted previously by De Souza et al . (). In general, bacterial isolates exhibiting multiple‐metal resistance had a considerably wider range of enzymatic activities (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies on Antarctic bacterial isolates showed an inverse correlation between multiple-metal-resistant bacteria and enzymatic potential (De Souza et al 2007).…”
Section: Correlation Between Enzyme Activity Profile and Metal Resistmentioning
confidence: 85%
See 2 more Smart Citations
“…Other heavy metals present in diverse contaminated sites include arsenic, strontium and titanium (58,59). Most of these heavy metals are detrimental to living organisms but bacterial community analysis has shown that microorganisms can grow in the presence of these contaminants (21,60). Other bacterial species tend to grow in environments contaminated with petroleum-based oils or radionuclides (22,40,61).…”
Section: Bioremediation and Biodegradation Applicationsmentioning
confidence: 99%